USE OF NATURAL AND SYNTHETIC POLYMERS IN THE PRODUCTION OF CARBON SORBENTS - Voitko, Ihor; Svysch, Alina; Denysovych, Vasyl (Proceedings of National Aviation University (archive), 2018)
The main purpose of this article is to find a connection between the experimental physical and chemical properties obtained and sorption characteristics from other polymeric raw materials and products of their processing on carbon adsorbents. Methods of definition which were used in the work are the specific bulk mass, the content of volatile substances and ash content, the construction of isotherms of sorption and the calculation of the internal specific surface of methylene blue. Results: adsorbents derived from raw materials with a low specific bulk density and high ash content are shown to have relatively low values ​​of the specific internal surface and sorption capacity. The increased content of volatile substances in raw materials and carbonates contributes to the enhanced formation of sorption pores in activated materials. Discussion: choosing a polymeric raw material for the production of carbon sorbents it is necessary in addition to other criteria to take into account its physical and chemical characteristics.